P2_3 PREM reigns suPREMe - Murgatroyd, Conan; Mott, Dan; Kinsman, Charlie; Stinton, James (Physics Special Topics, 2021)
This paper verifies that the distribution of mass of the Earth described by the density equations outlined in the PREM model are correct by utilizing them to calculate the moment of inertia of the Earth as 8.117 × 10(37) kg m^2. This was then found to be within 1% of the known value of the Earth’s moment of inertia, 8.038 × 10(37)kg m^2.